Sabanero sound and paisa sound: the production of tropical music in Medellín during the sixties. (2020)
In this second book by researcher Juan Sebastián Ochoa Escobar, the interaction between traditional and popular Colombian music that gave rise to the consolidation of the musical work of different groups and individuals is correctly analyzed. This text examines the role of the cultural industry in the configuration of specific sounds in the coastal and paisas regional contexts.